Effect of Tamarind Seeds on the Reduction of BOD and TSS of Tofu Factory Liquid Waste - Hurip Jayadi; Virna Diaz Pratama; Denok Indraswati; Sujangi; Lilis Prihastini; Hery Kusmantoro (Poltekkes Kemenkes Surabaya, 2025)
Liquid waste from the tofu industry is one of the significant sources of pollution in Indonesia, with high BOD and TSS content. High BOD and TSS can damage environmental quality and aquatic ecosystems if not managed properly. This study aims to evaluate the effectiveness of tamarind seed core in reducing BOD and TSS. The results showed that increasing the dose of tamarind seed and the coagulation-flocculation process time effectively reduced BOD and TSS. A dose of 8 g/L with 45 minutes resulted in a reduction of BOD by 64.8% and TSS by 60.3%. Increasing the coagulant dose accelerates the flocculation and adsorption process, thereby reducing contaminants. The use of tamarind seed as a natural coagulant shows an environmentally friendly potential for industrial wastewater treatment. Tamarind seeds are effective as a biocoagulant in reducing BOD and TSS of tofu factory wastewater, with higher doses and process time giving the best results.